Organometallic flow chemistry: solvento complexes. Issue 45 (2nd November 2022) - Frogley, Benjamin J.; Hill, Anthony F.; Onagi, Hideki; Watson, Lachlan J.
Abstract : In-flow photochemical methods allow the convenient synthesis 'on-demand' of ubiquitous tetrahydrofuran organometallic solvento complexes, e.g., [M(THF)(CO)5] (M = Cr, Mo, W) and [M(THF)(CO)2(η-L)] (M = Mn, Re; L = C5H5, C5H4Me, C5 Me5 ). Abstract : Photolysis under optimised flow conditions of metal carbonyls [L n M(CO) x ] [L n M(CO) x = Cr(CO)6, Mo(CO)6, W(CO)6, Mn(CO)3 (η-C5 H4 Me), Re(CO)3 (η-C5 H5 )] in tetrahydrofuran (THF) conveniently affords the synthetically versatile and labile solvento complexes [L n M(CO) x −1 (THF)], thereby obviating many of the caveats associated with photochemical syntheses using either 'batch' or falling film techniques. Conversions were optimised and yields assayed by a combination of in situ infrared spectroscopy and derivatisation as the corresponding triphenylphosphine complexes [L n M(CO) x −1 (PPh3 )].